X-Men : evolution - Grayson, Devin K.; Faerber, Jay (X-Men, 2020)
A complete collection of the Marvel Comics based on the hit cartoon series, X-Men evolution, contains tales of how two best friends become archenemies, a goddess from Africa finds her place in the world, and a man without a past decide mankind's future, as well as stories featuring Professor X, Magneto, Storm, Wolverine, Mystique, Rogue, and Beast.